The Development of Veterinary Clinic Management System Using Structured Approach - Jaffar, Nurnajlaa Bahirah; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2021)
Nowadays, with the development of information technology, services process in an institution become more effective and efficient. The same goes for services in veterinary clinics that require the advantages of information technology to support the management of information and services. Thus, veterinary clinic management system was developed for the V Care Animal Clinic. This is due to some problems faced by veterinary clinic clients such as the difficulty of using printed forms to fill in recurring information. Another problem is the difficulty of making appointments for animals and clients do not know the treatment options provided by veterinary clinic. The new system was developed with an iterative model and system design based on structured approach. The language that had been selected for this project was hypertext pre-processor (PHP) and other software used for this project are notepad as a programming tool, lucidchart, XAMPP as a platform to access the database and for webserver, MySQL which is for design and build database and lastly is Microsoft window 10 as an operating system. There are three users for this new system which are the Administrator of the clinic, clinic’s staff and clients of the clinic. Moreover, this system provide functions likes clinic information, appointments details about treatment packages for animals, schedule for booking appointments, online payments and provide appointment notification as a reminder for clients. Therefore, this system will help veterinary clinic’s clients of making appointment at time that most convenient and will help all the user of system to save time.